Competitiveness Strategy of Culinary Msmes Based on Swot Analysis: A Case Study of Bathok’s Coffee - Diajeng Fatikasari; Rita Mutiarni (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2025)
Micro, small, and medium enterprises (MSMEs) are required to continuously adapt to dynamic market conditions and increasing competition. This study aims to analyze the internal and external environments of Bathok’s Coffe and to formulate appropriate business development strategies using an integrated SWOT analysis approach. A descriptive qualitative method was employed, with data collected through observation, interviews with the business owner, and documentation. The analysis was supported by the Internal Factor Evaluation (IFE) Matrix, External Factor Evaluation (EFE) Matrix, Internal–External (IE) Matrix, and Grand Strategy Matrix. The results indicate that Bathok’s Coffe possesses internal strengths related to product quality and customer loyalty, while weaknesses are identified in marketing management and technology utilization. The integration of internal and external factors places the enterprise in a moderate strategic position, suggesting a hold-and-maintain strategy. This study concludes that strengthening internal capabilities and selectively utilizing market opportunities are essential for achieving sustainable business development.